1999
DOI: 10.1086/302197
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of Remains of a 2,000-Year-Old Human Population in China—and Its Relevance for the Origin of the Modern Japanese Population

Abstract: We extracted DNA from the human remains excavated from the Yixi site ( approximately 2,000 years before the present) in the Shandong peninsula of China and, through PCR amplification, determined nucleotide sequences of their mitochondrial D-loop regions. Nucleotide diversity of the ancient Yixi people was similar to those of modern populations. Modern humans in Asia and the circum-Pacific region are divided into six radiation groups, on the basis of the phylogenetic network constructed by means of 414 mtDNA ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 19 publications
(16 reference statements)
2
41
0
Order By: Relevance
“…The origin of the Jomon people is complicated by the variety of different research methods that have been used. Some cranial and dental studies have led researchers to posit that these populations derived from Southeast Asia (Turner, 1976(Turner, , 1989(Turner, , 1990(Turner, , 1992Hanihara, 1990Hanihara, , 1992aHanihara, , b, 1993Matsumura, 1994Matsumura, , 1995bMatsumura, , 2000aMatsumura and Hudson, 2005) and mitocondorial DNA analysis (Horai et al, 1991), while other studies based on genetic comparisons have suggested a Northeast Asian origin (Omoto, 1995;Omoto and Saitou, 1997;Oota et al, 1999). In the meantime, the distinctiveness of their non-metric cranial traits has obscured the possible ancestry of the Jomon (Shigematsu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the Jomon people is complicated by the variety of different research methods that have been used. Some cranial and dental studies have led researchers to posit that these populations derived from Southeast Asia (Turner, 1976(Turner, , 1989(Turner, , 1990(Turner, , 1992Hanihara, 1990Hanihara, , 1992aHanihara, , b, 1993Matsumura, 1994Matsumura, , 1995bMatsumura, , 2000aMatsumura and Hudson, 2005) and mitocondorial DNA analysis (Horai et al, 1991), while other studies based on genetic comparisons have suggested a Northeast Asian origin (Omoto, 1995;Omoto and Saitou, 1997;Oota et al, 1999). In the meantime, the distinctiveness of their non-metric cranial traits has obscured the possible ancestry of the Jomon (Shigematsu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Because of technical difficulties, most of the ancient DNA data available regarding the origin of peoples in the Japanese Archipelago are mitochondrial DNAs, [63][64][65][66][67][68][69][70][71] with exceptions of the ABCC11 gene 72 and the ABO blood group gene. 73 If the genome-wide nuclear DNA polymorphism data can be obtained for ancient DNA samples found from the Japanese Archipelago, we will be able to have a much wider scope on the history of peoples in this Archipelago.…”
Section: Perspectivesmentioning
confidence: 99%
“…73,74 Many previous studies have been carried out on the control region sequence types of ancient populations that existed geographically close to the Doigahama Yayoi population, such as the northern Kyushu Yayoi and the ancient Chinese populations. 52,[75][76][77] In this study, we analyzed the control region for examining the genetic structure of the Doigahama Yayoi population. As a preliminary analysis of the phylogenetic relationships of the Doigahama Yayoi population, the HVI sequence types obtained in this study were compared with those of the northern Kyushu Yayoi, modern Japanese and ancient Chinese populations that have previously been reported by other researchers, and a phylogenetic network was constructed to outline the phylogenetic characteristics of the Doigahama Yayoi population.…”
Section: Resultsmentioning
confidence: 99%
“…76 The segments from the 35 specimens from the Kuma-Nishioda Yayoi site in northern Kyushu 52 and 50 modern Japanese specimens 57 were added as objects of comparison in the Japanese archipelago. Moreover, segments from 13 specimens from the 2500-year-old Linzi population (Shandong province, China) 77 and 34 specimens from the 2000-yearold Linzi population 75 were added as East-Asian populations contemporary with the Yayoi populations (Figure 2).…”
Section: Resultsmentioning
confidence: 99%